Post-COVID policy shifts in higher education: A mixed-methods cross-sectional case study on rhetoric vs. Reality in digital transformation efforts. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background The COVID-19 pandemic accelerated digital transformation in higher education globally. In South Africa, universities swiftly adopted policies promoting inclusive, technology-driven teaching and learning. However, despite these policy shifts, a significant gap remains between institutional rhetoric and practical implementation. Digital inequality, insufficient staff training, and infrastructure limitations continue to hinder meaningful and sustainable transformation. Methods A mixed-methods cross-sectional case study was conducted across three South African universities. Quantitative data were collected through an online survey administered to 150 academic staff, with 132 valid responses analysed using descriptive statistics and cross-tabulations. Qualitative data were gathered through 12 in-depth interviews with policymakers, IT staff, and academic personnel. Thematic analysis was used to interpret qualitative findings and triangulate them with survey data. Results Survey data revealed that 82% of institutions had adopted digital transformation policies, yet only 46% of staff reported receiving sufficient training to implement them effectively. Additionally, 61% identified student internet access as a persistent barrier. Respondents were 58% female and 42% male, with most being academic staff (64%). Interview insights from 18 participants across seven public universities highlighted a disconnect between top-down narratives of smooth digital adaptation and ground-level experiences of uncoordinated rollouts, infrastructure deficits, and resistance to change. Temporary innovations, such as hybrid classrooms and data subsidies, were inconsistently applied and lacked long-term support. Conclusion Post-COVID digital policies in South African higher education remain ambitious but fragmented. Despite progress, implementation continues to be undermined by systemic and operational challenges. True digital transformation requires more than policy declarations—it demands cohesive leadership, cultural change, and sustainable resource allocation. Recommendations Universities should invest in long-term digital infrastructure, ongoing staff development, and equitable student support. Institutional accountability mechanisms must be embedded to monitor implementation. A multi-stakeholder, collaborative approach is essential to bridging the gap between policy and practice in the digital age.